TRIPOLI-4® calculations of neutron multiplicity counting rates of 3He array detectors and verification tests of an automatic MCNP-to-TRIPOLI conversion tool for recent ICSBEP subcritical experiments - Lee Yi-Kang (EPJ Web of Conferences)
TRIPOLI-4® is a general-purpose Monte Carlo radiation transport code developed at CEA Paris-Saclay center. It uses continuousenergy nuclear data to simulate neutron transport for diverse nuclear engineering fields. Neutron multiplication calculations of subcritical systems are important for application areas including criticality safety, reactor ex-core monitoring, and non-proliferation of nuclear materials. Subcritical experiments were performed by the LANL teams to improve subcritical simulation capabilities of MCNP code and to validate 3He based array detectors. Three of these experimental series based on Ni, W, and Cu reflected Pu spheres and related MCNP calculations were published on 2020 ICSBEP handbook. New automation conversion tool of MCNP geometries to TRIPOLI-4® ones has been available. In this study, the traditional manual modelling of above Pu-W and Pu-Cu cases (17 configurations including Cu and polyethylene reflectors) was first prepared. The MCNP/TRIPOLI-4® converted ones were secondly set for Pu-Cu cases. Finally the singles counting rate R1 (cts/s) in a single NPOD detector for Pu-W cases and in two NoMAD detectors for Pu-Cu cases were calculated. Generally, a good agreement of R1 was obtained between the TRIPOLI-4® calculations and the ICSBEP reported results. When using the polyethylene reflector layers in some Pu-Cu experiments, a difference of 5 to 16 % for R1 was observed between TRIPOLI-4 (Converted) results and the ICSBEP measured ones.